Fault Analysis and Solution of the Brake of an Automatic Transmission - Shi Yanhui; Feng Guangjun; Zhao Kai; Yu Dingyue; Wang Mingcheng (Jixie chuandong)
The failure of friction plate and steel disc in the brake of an automatic transmission is analyzed profoundly. The wave shape deformation of steel disc is caused by the thermal load distributing in its inner radius area. With checking the design,assemble,manufacture,heat-treatment and part quality,the main causes of failure is concerned with little thickness of steel disc,unreasonable design of supporting structure and large difference in characteristics of wave spring. The lifetime of the brake is markedly improved by optimizing the thickness of steel disc with the software ANSYS,filtering and using wave spring in groups. For finishing the durability test of an automatic transmission on the bench,the fault for the brake is effectively solved.